Pengaruh Indeks Pembangunan Manusia, Tenaga Kerja, dan Tabungan terhadap Pertumbuhan Ekonomi Kab/Kota di Provinsi Jawa Tengah Tahun 2017-2021 - Mia Arisma; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2024)
Economic Growth is an important indicator for determining the welfare of regional or state development. This research aims to determine the influence of human development, labor, and savings indices on the economic growth of districts/cities in Central Java Province in 2017 – 2021. The method in his research uses panel data analysis with a multiple linear regression fixed effect model. The independent variables in this research are the human development index, labor force, and savings. Meanwhile, the dependent variable is economic growth using GDP rate data for 35 districts/cities in Central Java Province for 2017 – 2021. The research results show that partially the human development index variable has a positive and significant effect on economic growth, labor has no effect on economic growth, and savings has a negative and significant effect on economic growth. Simultaneously, the human development index, labor, and savings variables influenced the economic growth of districts/cities in Central Java Province in 2017–2021.